Collaborative Planning and Governance in Urban Renewal: Community Based Neighborhood Development, Pınar Mahallesi, Sarıyer, İstanbul - Safiye Özge Subaşı; Büşra Metin (Sketch: Journal of City and Regional Planning, 2020)
After the 1980s, urban renewal has gained conceptually and practically importance with the process of reproducing urban spaces as a result of globalization and neoliberal policies. An overview of Turkey's urban renewal experiences has revealed that the interventions were developed by prioritizing physical improvements regardless of social and institutional dimensions. This study focuses on the Pınar neighborhood in İstanbul as the area holds a potential for a renewal project with its ownership structure and central location. The collaborative governance model, introduced by Chris Ansell and Alison Gash by examining 137 collaborative processes, was adapted to Pınar Neighborhood and a collaborative renewal process was designed with a community-based planning approach. Preparation, investigation and decision-making and implementation are developed as three main stages in the process. All stages in the process are supported by the principles of good governance to ensure maximum participation and consensus. This paper aims to provide alternative solutions based on neighborhood characteristics, to ensure the active participation of all stakeholders, and to be flexible and sustainable with the feedback mechanism it contains by considering the current legal framework in the process design. In the context of the collaborative governance model, not only physical but also institutional, social and economic development is provided by supporting trust-building, commitment to process, face-to-face dialogue and shared understanding.